Optimalisasi Kemampuan Manajerial untuk Meningkatkan Kinerja UMKM - Serlina Nur Indriyani; Ahmad Lukman Nugraha (Yayasan Al Ma'arif Dawuhan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy, contributing significantly to Gross Domestic Product (GDP), employment absorption, and domestic investment. However, MSMEs in Grobogan Regency face declining revenues due to limited managerial capabilities. Managerial skills, including planning, organizing, data-driven decision-making, and supervision, are critical for addressing operational and market challenges. This study aims to optimize MSME managerial capabilities in marketing and financial management to improve business performance. Using a qualitative descriptive approach, data were collected through semi-structured interviews, library research, and observations of MSME actors in Grobogan Regency. The findings indicate that inadequate financial management and the lack of technology-based marketing strategies are major barriers for MSMEs. Practical solutions include financial management training, risk management, digital marketing strategies, and technology adoption. Government support is also crucial in providing training programs, online marketing platforms, and funding schemes. Strengthening managerial competencies is expected to enhance MSME competitiveness and sustainability in Grobogan. This study provides practical recommendations to reinforce MSME existence and contribute to sustainable local economic growth.